Flexural and time dependent behavior of palm shell aggregate concrete beam - Chin, T.Y (Universiti Malaysia Sarawak, UNIMAS, 2009)
In recent years, many researches had been conducted to observe the performance of oil palm shell concrete. Oil palm shell is a natural lightweight material to replace coarse aggregate in concrete. Utilizing of oil palm shell as coarse aggregate not only can reduce the construction cost but also reduce the pollution problem due to palm shell waste. This study aims to investigate the flexural and time dependent behavior of palm shell aggregate concrete beam. In this laboratory work, two reinforced palm shell aggregate concrete beams were cast. Flexural and time dependent behavior of the beams was studied by applied increasing load and sustained load on the beams respectively. The report focus on the deflection results on these two beams. The experimental results were compared with the theoretical results. Overall results indicated that, oil palm shell can considered as a good replacement of coarse aggregate in concrete because it does not deflect very much under sustained load after a long time.